Preparation method of integrated and dual-channel PCNFs / ZIF8-SA composite aerogel as well as product and application of integrated and dual-channel PCNFs / ZIF8-SA composite aerogel

By using integrated, dual-path PCNFs/ZIF8-SA composite aerogel, the problem of evaporators being easily blown by sea breeze and salt crystals being blocked by the channels in solar seawater desalination technology is solved, and efficient and stable seawater desalination and resistance are achieved. The wind reverses.

CN119465630AActive Publication Date: 2025-02-18FUJIAN AGRI & FORESTRY UNIV

Patent Information

Application Number
CN202411354913.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-18
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

In the existing solar seawater desalination technology, the evaporator is easily blown over by the sea breeze, the evaporation efficiency is unstable, and salt crystals block the channel, affecting efficiency.

Method used

The integrated, dual-path PCNFs/ZIF8-SA composite aerogel is used to prepare aerogel with freshwater pathway and salt extraction pathway through directional refrigeration technology. The hydrophobic layer is located on the water surface and the side is a salt extraction pathway to avoid salt blockage. .

Benefits of technology

The evaporation efficiency of seawater desalination and the stability of aerogel are improved, and salt crystals are prevented from blocking the channels, achieving wind reversal and efficient evaporation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465630A_ABST
    Figure CN119465630A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an integrated and dual-channel PCNFs / ZIF8-SA composite aerogel and a product and application thereof, and the preparation method comprises the following steps: step 1, adding sodium alginate SA and ZIF-8 into a PCNFs suspension, and stirring until the SA is fully dissolved until a uniform mixed solution is formed; the PCNFs is PAN / ZIF-8 / lignin / NaCl carbon nanofibers after hydrophilic modification, and the pH value of the PAN / ZIF-8 / lignin / NaCl carbon nanofibers is 7-8; step 2, pouring the mixed solution into a mold, and performing directional freezing in a freeze dryer to obtain a composite aerogel columnar structure with a directional channel structure; 3, hydrophobic modification is conducted on the upper layer of the composite aerogel columnar structure, a hydrophobic layer with a certain thickness is formed, the lower layer of the composite aerogel columnar structure is a hydrophilic layer, and the hydrophobic layer and the hydrophilic layer are integrated. The aerogel disclosed by the invention has a dual-channel integrated special structure including a fresh water channel and a salt extraction channel, accumulated salt can be extracted from a side channel while efficient solar seawater desalination is realized, an evaporation channel is prevented from being blocked, and the evaporation efficiency and the stability of the composite aerogel are well improved.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of composite aerogel materials, and in particular to a preparation method of an integrated, dual-channel PCNFs / ZIF8-SA composite aerogel, and a product and application thereof. [Background technology]

[0002] Traditional desalination technologies such as multi-stage flash evaporation, multi-effect distillation, and membrane technology have problems such as high energy consumption and environmental pollution. Solar-driven interfacial evaporation technology only uses sunlight and seawater to produce fresh water, and is a green and clean desalination technology. So far, many types of solar evaporators have been developed, such as evaporators based on hydrogels, membranes, plasmas and other materials. However, in actual use, these materials have many problems such as easy salt formation to block the evaporation channel, low reusability, and unstable evaporation efficiency. When desalination operations are carried out on the sea surface, the evaporator is easily blown over by strong sea breezes and stops working. In addition, these evaporators need to be connected to cotton cores for continuous water supply and need insulation materials for support. They have many components and need to be assembled, which is not conducive to industrial applications.

[0003] The problem of salt crystallization produced during the evaporation process is one of the important reasons that affect the efficiency of solar desalination. Salt precipitation on the surface of the evaporator will affect the light absorption performance and block the water channel, thereby reducing the evaporation efficiency. The current salt tolerance strategy is mainly to return salt ions into the water body, which not only leads to an increase in the salt concentration in the seawater, which is not conducive to the survival of marine organisms, but also ignores the processing and utilization of salt.

[0004] Sodium alginate (SA) is widely available, cheap, has excellent biodegradability and biocompatibility, and has abundant hydrophilic groups, making it an ideal material for preparing aerogels. In previous studies by the inventors, it was concluded that SA-based aerogels and membrane materials have excellent salt resistance and underwater oil pollution resistance (patent numbers: CN108905296B, CN106853296A). In order to improve the efficiency of solar desalination and improve its performance in actual seawater, the inventors' research group used SA as a substrate, and prepared an integrated, salt-side-collecting, wind-resistant and reversible dual-channel composite aerogel CNFs / ZIF8-SA for solar desalination through directional freezing technology and surface wettability regulation. [Summary of the invention]

[0005] The technical problem to be solved by the present invention is to provide a preparation method of an integrated, dual-channel PCNFs / ZIF8-SA composite aerogel, as well as its products and applications. The aerogel has a dual-channel, integrated special structure of a freshwater channel and a salt extraction channel. While achieving efficient solar seawater desalination, the accumulated salt can be extracted from the side channel to avoid clogging the evaporation channel, thereby greatly improving the evaporation efficiency and the stability of the composite aerogel.

[0006] The present invention is achieved in that:

[0007] A method for preparing an integrated, dual-channel PCNFs / ZIF8-SA composite aerogel, the method steps are as follows:

[0008] Step 1, adding sodium alginate SA and ZIF-8 to the PCNFs suspension, stirring until SA is fully dissolved, and forming a uniform mixed solution; the PCNFs are hydrophilically modified PAN / ZIF-8 / lignin / NaCl carbon nanofibers; the mass ratio of sodium alginate SA, ZIF-8 and PCNFs is: 1.5:0.3:0.5-4:1:3;

[0009] Step 2, pouring the mixed solution into a mold, placing it in a freeze dryer for directional freezing, and vacuum freeze drying at -80°C for 48 hours to obtain a composite aerogel columnar structure with a directional channel structure;

[0010] Step 3: The upper layer of the composite aerogel columnar structure is hydrophobically modified to form a hydrophobic layer with a certain thickness, and the lower layer is a hydrophilic layer, and the hydrophobic layer and the hydrophilic layer are integrated to obtain the PCNFs / ZIF8-SA composite aerogel.

[0011] 2. The method for preparing an integrated, dual-path PCNFs / ZIF8-SA composite aerogel according to claim 1, characterized in that the preparation process of ZIF-8 in step 1 is as follows:

[0012] 1.1. Preparation of ZIF-8: Dissolve zinc nitrate hexahydrate Zn(NO3)2·6H2O in methanol to prepare solution A, and then dissolve 2-methylimidazole 2-MIM in methanol to prepare solution B; then quickly mix solutions A and B, stir, centrifuge, collect the white precipitate, and dry to obtain ZIF-8.

[0013] Furthermore, the preparation process of the PCNFs suspension in step 1 is as follows:

[0014] 1.2. Preparation of PAN / ZIF-8 / lignin / NaCl electrospinning nanofiber membrane:

[0015] First, sodium chloride NaCl is added to N, N-dimethylformamide DMF solution, ball-milled and allowed to stand, the upper NaCl solution and DMF solution are added to a container, and ZIF-8 particles are added to the above solution. After ultrasonic treatment, polyacrylonitrile PAN is added and stirred for a period of time, and finally lignin is added and stirred at 100° C. to obtain an electrospinning precursor solution; the precursor solution is added to a syringe, and electrospinning is performed at a propulsion rate of 0.3-0.6 mL / h and 16-22 kV to obtain a PAN / ZIF-8 / lignin / NaCl nanofiber membrane with uniform diameter, which is dried at 60-80° C. for use;

[0016] 1.3. Preparation of PAN / ZIF-8 / lignin / NaCl electrospun carbon nanofiber membrane:

[0017] The PAN / ZIF-8 / lignin / NaCl nanofiber membrane was placed in a tubular furnace for high-temperature carbonization: first, the temperature was raised to 280°C at a heating rate of 5°C / min in a nitrogen atmosphere and maintained for 2 h, and then the temperature was raised to 900°C at a heating rate of 5°C / min in a nitrogen atmosphere and maintained for 2 h to obtain a PAN / ZIF-8 / lignin / NaCl carbon nanofiber membrane;

[0018] 1.4. Hydrophilic modification of PAN / ZIF-8 / lignin / NaCl carbon nanofiber membrane:

[0019] A certain volume of DA Tris-HCl buffer and ethanol are mixed and stirred to obtain a DA water / ethanol mixed solution; subsequently, the PAN / ZIF-8 / lignin / NaCl carbon nanofiber membrane is placed in the mixed solution and floated for 2-6 hours to achieve hydrophilic modification of the composite membrane, thereby obtaining a hydrophilically modified PAN / ZIF-8 / lignin / NaCl carbon nanofiber membrane;

[0020] 1.5. Preparation of PAN / ZIF-8 / lignin / NaCl carbon nanofibers:

[0021] The hydrophilically modified PAN / ZIF-8 / lignin / NaCl carbon nanofiber membrane was cut into thin slices and homogenized in deionized water at 12000-13000 rpm using a homogenizer to obtain a uniform suspension of PCNFs.

[0022] Furthermore, the preparation method of the composite aerogel columnar structure in step 2 is as follows: SA and ZIF-8 are added to the PCNFs suspension, stirred until SA is fully dissolved, and a uniform mixed solution is formed; the mixed solution is poured into a polytetrafluoroethylene mold placed on a copper block, the copper block and the mold are placed in a Dewar flask, liquid nitrogen is added, and after freezing, the sample is immediately transferred to a freeze dryer, and vacuum freeze-dried at -80°C for 48 hours to obtain a composite aerogel columnar structure with a directional channel structure.

[0023] Furthermore, the hydrophobic modification of the upper layer of the composite aerogel columnar structure in step 3 is specifically as follows: prepare a 2% mass fraction of methyltrimethoxysilane MTMS solution, connect it with the upper layer of the composite aerogel columnar structure, and hydrophobically modify the aerogel so that a hydrophobic layer with a certain thickness is formed on the upper layer of the composite aerogel columnar structure, and the lower layer is a hydrophilic layer, and the hydrophobic layer and the hydrophilic layer are integrated to obtain PCNFs / ZIF8-SA composite aerogel.

[0024] Furthermore, the PCNFs / ZIF8-SA composite aerogel is a PCNFs / ZIF8-SA composite aerogel with asymmetric wettability, and the thickness of the hydrophobic layer is less than the thickness of the hydrophilic layer.

[0025] Furthermore, the thickness of the hydrophobic layer: the thickness of the hydrophilic layer = 1:1-1:7.

[0026] Furthermore, the preparation method described herein obtains an integrated, dual-channel PCNFs / ZIF8-SA composite aerogel.

[0027] Furthermore, the application of the integrated, dual-channel PCNFs / ZIF8-SA composite aerogel prepared by the preparation method is that the PCNFs / ZIF8-SA composite aerogel is used for solar seawater desalination; the PCNFs / ZIF8-SA composite aerogel has dual channels, the hydrophobic layer is located on the water surface, the top and the directional channel of the hydrophobic layer are freshwater channels, and the side of the hydrophobic layer is a salt extraction channel; in the process of seawater desalination, water is vaporized from the freshwater channel at the top into water vapor and escapes, and the accumulated salt is precipitated from the salt extraction channel on the side;

[0028] The hydrophilic layer is immersed in seawater for directionally transporting seawater to the hydrophobic layer.

[0029] Furthermore, a layer of polyamide nanofiltration membrane is set at the bottom of the PCNFs / ZIF8-SA composite aerogel to carry out solar seawater desalination and collect the salt extracted from the side; the aqueous solution is treated with carbonate to obtain battery-grade Li2CO3 powder, thereby realizing the collection of lithium ions in seawater.

[0030] The present invention has the following advantages:

[0031] The upper layer of the PCNFs / ZIF8-SA composite aerogel of the present invention is a hydrophobic layer, and its components include a photothermal conversion material PCNFs with a light absorption rate of 93%, which has high heat absorption and low thermal conductivity, and is conducive to solar interface evaporation. In the process of seawater desalination, water is vaporized from the top of the hydrophobic layer into water vapor and escapes, and the accumulated salt is precipitated from the side of the hydrophobic layer. The dual-channel structure composed of the fresh water evaporation channel and the salt extraction channel can effectively prevent salt from crystallizing on the surface of the hydrophobic layer, that is, the photothermal layer, and reducing the evaporation rate. The lower end of the PC NFs / ZIF8-SA composite aerogel of the present invention is a hydrophilic layer for directional water transportation, ensuring sufficient water supply during the evaporation process. The PCNFs / ZIF8-SA composite aerogel of the present invention has a multi-level pore structure, wherein the composite aerogel obtains parallel directional channels of about 30-50 μm by directional freezing, wherein PAN / ZIF-8 / lignin / NaCl carbon nanofibers of about 200 nm are penetrated in the directional channels, wherein the nanofibers have mesopores and micropore structures formed by pyrolysis of ZIF-8 and lignin, and furthermore, the PCNFs / ZIF8-SA composite aerogel is inlaid with a porous material ZIF-8 of about 50 nm in diameter. Due to the capillary effect, the parallel channels can continuously transport water from the bottom to the upper layer, and the introduction of carbon nanofibers and ZIF-8 increases the specific surface area and porosity of the PCNFs / ZIF8-SA composite aerogel, wherein the micropores and mesopores can reduce the interaction between water molecules, thereby reducing the evaporation enthalpy and greatly improving the interface evaporation rate.

[0032] In addition, the present invention can prepare an asymmetric wettability structure by regulating the wettability of the hydrophobic layer and the hydrophilic layer and the water entry height, ensuring that the aerogel can float on the sea surface without sinking, so that the PCNFs / ZIF8-SA composite aerogel has the characteristics of wind reversal resistance. In addition, the special structural design of the dual channels (fresh water channel and salt extraction channel) can realize efficient solar desalination while extracting the accumulated salt from the side channel to avoid blocking the evaporation channel, thereby improving the evaporation efficiency and the stability of the composite aerogel. At the same time, this composite aerogel can also be used to extract lithium from salt lakes to help resource reserves.

Brief Description of the Drawings

[0033] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings.

[0034] Figure 1 This is the SEM image of PCNFs in Example 1 of the present invention.

[0035] Figure 2 This is a flow chart for preparing the PCNFs / ZIF8-SA composite aerogel of the present invention.

[0036] Figure 3This is a schematic diagram of the PCNFs / ZIF8-SA composite aerogel structure of the present invention.

[0037] Figure 4 Schematic diagram of the wettability analysis of the PCNFs / ZIF8-SA composite aerogel of the present invention.

[0038] Figure 5 This is the UV-visible-near infrared absorption spectrum of the PCNFs / ZIF8-SA composite aerogel of the present invention.

[0039] Figure 6 This is a graph showing the evaporation rate of the PCNFs / ZIF8-SA composite aerogel of the present invention in 10 wt% salt water under 1 sunlight intensity.

[0040] Figure 7 This is a schematic diagram of the interface evaporation of the PCNFs / ZIF8-SA composite aerogel of the present invention.

[0041] Figure 8 This is a diagram showing the salt formation of the PCNFs / ZIF8-SA composite aerogel of the present invention before and after evaporation under different sunlight intensities and different salt concentrations.

[0042] Fig. 9 It is a schematic diagram of the cyclic stability test of the PCNFs / ZIF8-SA composite aerogel of the present invention under 1 sunlight intensity and 20% salt water. [Specific implementation method]

[0043] The following will be combined with the attached Figure 1-9 The technical scheme of the present invention is clearly and completely described in detail with specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0044] 1. Preparation of products

[0045] Embodiment 1:

[0046] This embodiment first provides a PAN / ZIF-8 / lignin / NaCl porous carbon nanofiber, and the preparation method thereof comprises the following steps:

[0047] 1. Preparation of ZIF-8

[0048] 4.461 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) was dissolved in methanol to prepare solution A, and 9.852 g of 2-methylimidazole (2-MIM) was dissolved in methanol to prepare solution B. Solutions A and B were quickly mixed, stirred, centrifuged, and the white precipitate was collected and dried to obtain ZIF-8.

[0049] 2. Preparation of PAN / ZIF-8 / lignin / NaCl electrospinning nanofiber membrane

[0050] First, NaCl was added to the DMF solution, ball-milled and allowed to stand, 0.5 mL of the upper NaCl solution and 5.5 mL of DMF solution were added to a beaker, and 0.6 g of ZIF-8 particles were added to the above solution. After ultrasonic treatment for 60 min, 0.35 g of PAN was added and stirred for 24 h, and finally 0.35 g of lignin was added and stirred at 100 ° C for 1 h to obtain an electrospinning precursor solution. The precursor solution was added to a syringe, and electrospinning was performed at a propulsion rate of 0.6 mL / h and 22 kV to obtain a PAN / ZIF-8 / lignin / NaCl nanofiber membrane with uniform diameter, which was dried at 80 ° C for use.

[0051] 3. Preparation of PAN / ZIF-8 / lignin / NaCl electrospun carbon nanofiber membrane

[0052] The PAN / ZIF-8 / lignin / NaCl nanofiber membrane was placed in a crucible and placed in a tube furnace for high-temperature carbonization. First, the temperature was raised to 280°C at a heating rate of 5°C / min in a nitrogen atmosphere and maintained for 2 h, and then the temperature was raised to 900°C at a heating rate of 5°C / min in a nitrogen atmosphere and maintained for 2 h to obtain a PAN / ZIF-8 / lignin / NaCl carbon nanofiber membrane.

[0053] 4. Hydrophilic modification of PAN / ZIF-8 / lignin / NaCl carbon nanofiber membrane

[0054] A certain volume of DA Tris-HCl buffer and ethanol were added to a beaker and magnetically stirred for 5 minutes to obtain a DA water / ethanol mixed solution. Subsequently, the PAN / ZIF-8 / lignin / NaCl composite membrane was placed in the above mixed solution and floated for 4 hours to achieve hydrophilic modification of the composite membrane.

[0055] 5. Preparation of PAN / ZIF-8 / lignin / NaCl carbon nanofibers

[0056] 0.5 g of the hydrophilically modified PAN / ZIF-8 / lignin / NaCl nanofiber membrane was cut into thin slices and homogenized in deionized water at 13000 rpm for 30 min using a homogenizer to obtain a uniform solution, which is a suspension of PCNFs. The scanning electron microscope image of the above PCNFs suspension is shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that after the carbonization of nanofibrils, ZIF-8 and lignin were pyrolyzed to form mesoporous and microporous structures.

[0057] Embodiment 2:

[0058] The differences from Example 1 are: in step 2, the propulsion rate is 0.5 mL / h, the voltage is 19 kV, the amount of DMF solution is 4 mL, and the amount of ZIF-8 is 0.4 g; in step 5, the amount of PAN / ZIF-8 / lignin / NaCl nanofiber membrane is 1 g, the speed of the homogenizer is 12000 rpm, and the other operations and amounts are exactly the same as in Example 1.

[0059] Embodiment 3:

[0060] The difference from Example 1 is that: in step 2, the propulsion rate is 0.3 mL / h, the voltage is 16 kV, the amount of DMF solution is 5 mL, and the amount of ZIF-8 is 0.5 g; in step 5, the amount of PAN / ZIF-8 / lignin / NaCl nanofiber membrane is 1.5 g, the speed of the homogenizer is 12500 rpm, and the other operations and amounts are exactly the same as in Example 1.

[0061] Embodiment 4:

[0062] The raw materials prepared in Example 1 are used to prepare PCNFs / ZIF8-SA composite aerogel, and the preparation method thereof comprises the following steps:

[0063] Add 1.5g SA and 0.3g ZIF-8 to the PCNFs suspension and stir until SA is fully dissolved until a uniform mixture is formed. Pour the mixture into a polytetrafluoroethylene mold on a copper block, place the copper block and the mold in a Dewar flask, add liquid nitrogen, and immediately transfer the sample to a freeze dryer after freezing. Vacuum freeze-dry at -80°C for 48 hours to obtain an aerogel with a directional channel structure. Then prepare a 2% MTMS solution by mass to regulate the wettability of the aerogel: wet the filter paper with the hydrolyzed MTMS solution, and then cover the filter paper on the upper surface of the aerogel for 3s to obtain a PCNFs / ZIF8-SA composite aerogel with asymmetric wettability; the specific preparation process is as follows Figure 2 As shown; the structure of the prepared PCNFs / ZIF8-SA composite aerogel is as shown Figure 3As shown, the present invention performs hydrophobic modification on the upper layer of the composite aerogel columnar structure to form a hydrophobic layer 1 with a certain thickness, and the lower layer is a hydrophilic layer 2, and the PCNFs / ZIF8-SA composite aerogel is subjected to directional freezing to obtain a penetrating directional channel 3.

[0064] Embodiment 5:

[0065] The difference from Example 4 is that the amount of SA is 1 g, and the other operations and amounts are exactly the same as those in Example 4.

[0066] Embodiment 6:

[0067] The difference from Example 4 is that the amount of SA is 2 g, and the other operations and amounts are exactly the same as those in Example 4.

[0068] Embodiment 7:

[0069] The difference from Example 4 is that the filter paper is in contact with the aerogel surface for 10 seconds, and the other operations and dosages are exactly the same as those in Example 4.

[0070] Embodiment 8:

[0071] The difference from Example 4 is that the filter paper is in contact with the aerogel surface for 15 seconds, and the other operations and dosages are exactly the same as those in Example 12.

[0072] Embodiment 9:

[0073] The difference from Example 4 is that the filter paper is in contact with the aerogel surface for 20 seconds, and the other operations and dosages are exactly the same as those in Example 4.

[0074] The thickness of the hydrophobic layer and the hydrophilic layer of the PCNFs / ZIF8-SA composite aerogel prepared in the above example are shown in Table 1 below:

[0075] Table 1 Example hydrophobic layer, hydrophilic layer thickness and ratio

[0076] serial number Hydrophobic layer thickness (cm) Hydrophilic layer thickness (cm) Hydrophobic layer: Hydrophilic layer Example 4 0.5 3.5 1:7 Example 7 2 2 1:1 Example 8 3 1 3:1 Example 9 4 0 1:0

[0077] As can be seen from Table 1, the thickness of the hydrophobic layer after hydrophobic modification can be controlled by controlling the contact time between the MTMS solution wetting the filter paper and the aerogel surface.

[0078] 2. Performance measurement:

[0079] 1. The wettability analysis of the PCNFs / ZIF8-SA composite aerogel prepared in Example 4 was performed. The specific process is as follows: Figure 4 As shown, figure a is the asymmetric wettability diagram of PCNFs / ZIF8-SA composite aerogel; b is the water contact angle diagram of the upper surface hydrophobic layer and the underlying hydrophilic layer of PCNFs / ZIF8-SA composite aerogel.

[0080] from Figure 4 It can be seen that the contact angle of the hydrophobic layer surface is 138.21°, indicating that the hydrophobic layer surface of the prepared composite aerogel has good hydrophobicity. The hydrophilic layer surface of the composite aerogel quickly absorbs water within 70ms, indicating that the hydrophilic layer of the PCNFs / ZIF8-SA composite aerogel has good hydrophilicity. During the evaporation process, the composite aerogel can quickly replenish water from the water body below, avoiding the situation in which the amount of evaporated water per unit time is greater than the amount of replenished water, which reduces the evaporation rate.

[0081] 2. The light absorption capacity of PCNFs / ZIF8-SA composite aerogel was tested using UV-visible spectrophotometer. Figure 5 As shown. Figure 5 It can be seen that within the wavelength range of 250-2500nm, the light absorption rate of the photothermal layer of the PCNFs / ZIF8-SA composite aerogel of the present invention can reach 93%, which indicates that the PCNFs / ZIF8-SA composite aerogel has excellent light absorption performance.

[0082] 3. A layer of commercial polyamide nanofiltration membrane was added to the bottom of the PCNFs / ZIF8-SA composite aerogel prepared in Example 4 to conduct a solar desalination experiment. Figure 6 As shown. Figure 6 It can be seen that under 1 sun intensity and 10 wt% salt water, the evaporation rate of PCNFs / ZIF8-SA composite aerogel is maintained at 2.297 kg m -2 h -1 ~2.36kg m - 2 h -1 Since the particle size of divalent ions is much larger than that of monovalent ions, the use of polyamide nanofiltration membrane can make Na + , Li + , K + ions pass through, while Mg in seawater 2+ , Ca 2+ Ions are intercepted by the nanofiltration membrane in the water body. During the interfacial evaporation process, Na + , Li + , K + As water molecules enter the PCNFs / ZIF8-SA composite aerogel from bottom to top, water evaporates at the top of the composite aerogel due to heat, and the accumulated salt precipitates from the side of the hydrophobic layer, such as Figure 7 As shown, Figure 7Figure a shows the macroscopic surface of PCNFs / ZIF8-SA composite aerogel before interface evaporation; Figure b shows the salt crystals extracted from the side passage of PCNFs / ZIF8-SA composite aerogel after interface evaporation. The salts extracted from the side are collected, and the salt crystals at this time are NaCl, LiCl, and KCl. The aqueous solution is treated with carbonate to obtain battery-grade Li2CO3 powder, which helps to reserve lithium resources.

[0083] 4. The PCNFs / ZIF8-SA composite aerogel prepared in Example 5 was placed in 3.5 wt% salt water under 1 sun intensity for seawater desalination experiment. After evaporation for 12 h, the evaporation rate was calculated to be 3.462 kg m -2 h -1 The reason why PCNFs / ZIF8-SA composite aerogel can achieve a high freshwater vaporization rate is that during the evaporation process, the accumulated salt crystallizes on the side of the hydrophobic layer and does not block the freshwater evaporation channel.

[0084] 5. In the application of seawater desalination and simulated high-concentration salt water evaporation, the PCNFs / ZIF8-SA composite aerogel of the present invention has a high evaporation rate, see Figure 8 As shown in the figure, a is the initial state of PCNFs / ZIF8-SA composite aerogel. Under 1 sun intensity and in 3.5wt% salt water, PCNFs / ZIF8-SA composite aerogel has no obvious salt crystallization after the 30min evaporation experiment (as shown in Figure 1). Figure 8 b); in 20 wt% salt water under 6 sun intensity, after 30 min evaporation experiment, only part of the salt crystallized on the side of PCNFs / ZIF8-SA composite aerogel, which did not affect the light absorption of the aerogel surface (such as Figure 8 c). In addition, the stable evaporation rate of PCNFs / ZIF8-SA composite aerogel in 20 wt% salt solution under 1 sun intensity is 2.293 kg m -2 h -1 , which is higher than the evaporation rate of some evaporators currently reported in 3.5wt% salt solution under 1 sun intensity.

[0085] 5. The PCNFs / ZIF8-SA composite aerogel of the present invention has good cyclic stability. The PCNFs / ZIF8-SA composite aerogel was placed in a 20wt% salt solution under 1 sun intensity for cyclic testing. The results are as follows: Fig. 9 As shown. Fig. 9 It can be seen that the composite aerogel of the present invention can stably operate for 20 cycles, and the evaporation rate is 1.975 kg m -2 h -1 -2kg m -2 h -1, the evaporation rate is almost constant, which indicates that the PCNFs / ZIF8-SA composite aerogel has good stability.

[0086] 6. Wind reversal resistance: When the wind reversal resistance test was conducted by simulating sea surface wind, the wind force of the electric fan could reach a maximum equivalent to the level 3 wind in nature. At this time, the PCNFs / ZIF8-SA composite aerogel prepared in Example 4 floated stably on the water surface. In the absence of storms or special weather conditions, the wind force on the sea surface is usually between level 1 and level 3. Therefore, the PCNFs / ZIF8-SA composite aerogel of the present invention can float on the sea surface without capsizing, and has a certain wind reversal resistance.

[0087] In summary, the present invention has the following advantages:

[0088] 1. The present invention uses SA as the aerogel substrate, which is low in price, has excellent biodegradability and biocompatibility, and will not damage the environment; SA has abundant hydrophilic groups, can quickly transmit water, and ensure a stable water supply during the evaporation process; SA has good salt resistance and good underwater anti-oil performance, so that the composite aerogel can remain clean in real seawater without affecting the evaporation efficiency.

[0089] 2. The present invention introduces carbonized, modified and homogenized PAN / ZIF-8 / lignin / NaCl carbon nanofibers (PCNFs) in the aerogel preparation process to strengthen the multi-level pore structure for nano-confinement ( Figure 1 ). After carbonization of nanofibrils, ZIF-8 and lignin are pyrolyzed to form mesoporous and microporous structures, which provide high specific surface area and porosity. The micropores and mesopores can reduce the interaction between water molecules, thereby reducing the evaporation enthalpy and increasing the interfacial evaporation rate.

[0090] 3. The directional channel 3 of the PCNFs / ZIF8-SA composite aerogel prepared by the directional freeze-drying technology of the present invention is 30-50 μm in size, has a good capillary effect, and can continuously transport water from the bottom to the upper layer to ensure sufficient water supply during evaporation. At the same time, ZIF-8 with an average diameter of about 50 nm is embedded in the PCNFs / ZIF8-SA composite aerogel, which plays a role of nano-confinement on water molecules, better reduces the evaporation enthalpy, and saves energy. Since ZIF-8 is a porous material with a high specific surface area, penetrating it into the PCNFs / ZIF8-SA composite aerogel can promote the transmission of water vapor, reduce the resistance of water vapor during the transmission process, and thus increase the evaporation rate.

[0091] 4. The upper layer of the PCNFs / ZIF8-SA composite aerogel of the present invention is a hydrophobic layer 1, and the lower layer is a hydrophilic layer 5. During the evaporation process, the composite aerogel can quickly replenish water from the water body below through the hydrophilic layer 2, avoiding the situation in which the amount of evaporated water per unit time is greater than the amount of replenished water during the evaporation process, thereby reducing the evaporation rate.

[0092] 5. Most of the existing evaporators are composed of a photothermal layer, a water transfer layer, a support layer, an insulating layer and a water transfer cotton core. They have many components and cannot achieve self-floating and wind-resistant reversal functions on the sea surface. The PCNFs / ZIF8-SA composite aerogel of the present invention is integrated, and the hydrophobic layer 1 (which also has a photothermal effect) and the hydrophilic layer 2 (which plays a water transfer role) are a whole. The traditional hydrophobic modification method is to immerse the aerogel directly in the solution. Due to the high siphon rate of the aerogel, it quickly absorbs the solution and it is difficult to control the thickness of the hydrophobic layer. The present invention moistens the filter paper with MTMS solution, and then covers the filter paper on the upper surface of the aerogel for modification, which can reduce the siphon rate of the aerogel and adjust the aerogel to obtain aerogels with different hydrophobic layer thicknesses. In addition, the PCNFs / ZIF8-SA composite aerogel is light in weight, 11cm 3 The composite aerogel has a mass of 0.5 g and can be supported by a dandelion. Its structural characteristics of thin hydrophobic layer 1 and thick hydrophilic layer 2 enable it to float on the sea surface and have the characteristics of wind reversal resistance. During the evaporation process, only the hydrophobic layer floats on the water surface, and the hydrophilic layer is submerged in the water and has a certain weight, so it is not easy to overturn. Therefore, the PCNFs / ZIF8-SA composite aerogel of the present invention can float on the sea surface without overturning, and has a certain wind reversal resistance.

[0093] 6. The PCNFs / ZIF8-SA composite aerogel of the present invention has a high evaporation rate, which is due to the special design of the dual channels: water vaporizes from the top of the hydrophobic layer, and salt is extracted from the side of the hydrophobic layer to avoid blocking the evaporation channel of seawater desalination. In addition, in 3.5wt% to 20wt% salt solution, the evaporation rate of the PCNFs / ZIF8-SA composite aerogel remains stable, indicating that the PCNFs / ZIF8-SA composite aerogel has good salt resistance and is suitable for interfacial evaporation of high-concentration salt water.

[0094] 7. The PCNFs / ZIF8-SA composite aerogel of the present invention has good cyclic stability, which is due to: (1) the design of the dual-channel PCNFs / ZIF8-SA composite aerogel. The dual channels of the freshwater channel and the salt side mining channel ensure that the evaporation channel of the PCNFs / ZIF8-SA composite aerogel will not be blocked by salt crystals, so that the composite aerogel maintains good stability; (2) thanks to the good salt resistance and underwater anti-oil performance of SA, the PCNFs / ZIF8-SA composite aerogel can remain clean in real seawater, so that the composite aerogel has long-term stability.

[0095] 8. The existing salt-tolerance strategy is to return the salt to the water body. When large-scale seawater desalination is carried out, the salt ion concentration in the seawater will increase, affecting the living environment of marine organisms. In addition, the processing and utilization of salt crystals are missed. Unlike the former, the salt precipitated in the process of solar seawater desalination in the present invention will not flow back into the water body. Its crystallization is on the side of the PCNFs / ZIF8-SA composite aerogel, which can prevent the vaporization channel from being blocked by salt crystals and affect the evaporation rate. At the same time, the salt precipitated on the side can be collected and separated by chemical precipitation to obtain lithium. After purification, it can be used in the battery industry, which is expected to alleviate the problem of lithium supply shortage.

[0096] Although the specific implementation modes of the present invention are described above, those skilled in the art should understand that the specific implementation modes described are only illustrative and are not intended to limit the scope of the present invention. Equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.

Claims

1. A method for preparing an integrated, dual-channel PCNFs / ZIF8-SA composite aerogel, characterized in that: The method steps are as follows: Step 1, adding sodium alginate SA and ZIF-8 to the PCNFs suspension, stirring until SA is fully dissolved, and forming a uniform mixed solution; the PCNFs are hydrophilically modified PAN / ZIF-8 / lignin / NaCl carbon nanofibers; the mass ratio of sodium alginate SA, ZIF-8 and PCNFs is: 1.5:0.3:0.5-4:1:3; Step 2, pouring the mixed solution into a mold, placing it in a freeze dryer for directional freezing, and vacuum freeze drying at -80°C for 48 hours to obtain a composite aerogel columnar structure with a directional channel structure; Step 3: The upper layer of the composite aerogel columnar structure is hydrophobically modified to form a hydrophobic layer with a certain thickness, and the lower layer is a hydrophilic layer, and the hydrophobic layer and the hydrophilic layer are integrated to obtain the PCNFs / ZIF8-SA composite aerogel.

2. The method for preparing an integrated, dual-path PCNFs / ZIF8-SA composite aerogel according to claim 1, characterized in that: The preparation process of ZIF-8 in step 1 is as follows: 1.

1. Preparation of ZIF-8: Dissolve zinc nitrate hexahydrate Zn(NO3)2·6H2O in methanol to prepare solution A, and then dissolve 2-methylimidazole 2-MIM in methanol to prepare solution B; then quickly mix solutions A and B, stir, centrifuge, collect the white precipitate, and dry to obtain ZIF-8.

3. The method for preparing an integrated, dual-path PCNFs / ZIF8-SA composite aerogel according to claim 1, characterized in that: The preparation process of the PCNFs suspension in step 1 is as follows: 1.

2. Preparation of PAN / ZIF-8 / lignin / NaCl electrospinning nanofiber membrane: First, sodium chloride NaCl is added to N, N-dimethylformamide DMF solution, ball-milled and allowed to stand, the upper NaCl solution and DMF solution are added to a container, and ZIF-8 particles are added to the above solution. After ultrasonic treatment, polyacrylonitrile PAN is added and stirred for a period of time, and finally lignin is added and stirred at 100° C. to obtain an electrospinning precursor solution; the precursor solution is added to a syringe, and electrospinning is performed at a propulsion rate of 0.3-0.6 mL / h and 16-22 kV to obtain a PAN / ZIF-8 / lignin / NaCl nanofiber membrane with uniform diameter, which is dried at 60-80° C. for use; 1.

3. Preparation of PAN / ZIF-8 / lignin / NaCl electrospun carbon nanofiber membrane: The PAN / ZIF-8 / lignin / NaCl nanofiber membrane was placed in a tubular furnace for high-temperature carbonization: first, the temperature was raised to 280°C at a heating rate of 5°C / min in a nitrogen atmosphere and maintained for 2 h, and then the temperature was raised to 900°C at a heating rate of 5°C / min in a nitrogen atmosphere and maintained for 2 h to obtain a PAN / ZIF-8 / lignin / NaCl carbon nanofiber membrane; 1.

4. Hydrophilic modification of PAN / ZIF-8 / lignin / NaCl carbon nanofiber membrane: A certain volume of DA Tris-HCl buffer and ethanol are mixed and stirred to obtain a DA water / ethanol mixed solution; subsequently, the PAN / ZIF-8 / lignin / NaCl carbon nanofiber membrane is placed in the mixed solution and floated for 2-6 hours to achieve hydrophilic modification of the composite membrane, thereby obtaining a hydrophilically modified PAN / ZIF-8 / lignin / NaCl carbon nanofiber membrane; 1.

5. Preparation of PAN / ZIF-8 / lignin / NaCl carbon nanofibers: The hydrophilically modified PAN / ZIF-8 / lignin / NaCl carbon nanofiber membrane was cut into thin slices and homogenized in deionized water at 12000-13000 rpm using a homogenizer to obtain a uniform suspension of PCNFs.

4. The method for preparing an integrated, dual-path PCNFs / ZIF8-SA composite aerogel according to claim 1, characterized in that: The preparation method of the composite aerogel columnar structure in step 2 is as follows: SA and ZIF-8 are added to the PCNFs suspension, and stirred until SA is fully dissolved, and a uniform mixed solution is formed; the mixed solution is poured into a polytetrafluoroethylene mold placed on a copper block, the copper block and the mold are placed in a Dewar flask, liquid nitrogen is added, and after freezing, the sample is immediately transferred to a freeze dryer, and vacuum freeze-dried at -80°C for 48 hours to obtain a composite aerogel columnar structure with a directional channel structure.

5. The method for preparing an integrated, dual-path PCNFs / ZIF8-SA composite aerogel according to claim 1, characterized in that: The hydrophobic modification of the upper layer of the composite aerogel columnar structure in step 3 is specifically as follows: prepare a 2% by mass methyltrimethoxysilane MTMS solution, connect it to the upper layer of the composite aerogel columnar structure, and hydrophobically modify the aerogel so that a hydrophobic layer with a certain thickness is formed on the upper layer of the composite aerogel columnar structure, and the lower layer is a hydrophilic layer, and the hydrophobic layer and the hydrophilic layer are integrated to obtain the PCNFs / ZIF8-SA composite aerogel.

6. The method for preparing an integrated, dual-path PCNFs / ZIF8-SA composite aerogel according to claim 1, characterized in that: The PCNFs / ZIF8-SA composite aerogel is a PCNFs / ZIF8-SA composite aerogel with asymmetric wettability, and the thickness of the hydrophobic layer is less than the thickness of the hydrophilic layer.

7. The method for preparing an integrated, dual-channel PCNFs / ZIF8-SA composite aerogel according to claim 6, characterized in that: The thickness of the hydrophobic layer: the thickness of the hydrophilic layer = 1:1-1:

7.

8. An integrated, dual-channel PCNFs / ZIF8-SA composite aerogel prepared according to the preparation method according to any one of claims 1 to 7.

9. An application of an integrated, dual-channel PCNFs / ZIF8-SA composite aerogel prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The PCNFs / ZIF8-SA composite aerogel is used for solar seawater desalination; the PCNFs / ZIF8-SA composite aerogel has dual passages, the hydrophobic layer is located on the water surface, the top of the hydrophobic layer and the directional channel are freshwater passages, and the side of the hydrophobic layer is a salt extraction passage; in the process of seawater desalination, water is vaporized into water vapor from the top freshwater passage and escapes, and the accumulated salt is precipitated from the side salt extraction passage; The hydrophilic layer is immersed in seawater for directionally transporting seawater to the hydrophobic layer.

10. The use of an integrated, dual-channel PCNFs / ZIF8-SA composite aerogel according to claim 9, characterized in that: A layer of polyamide nanofiltration membrane is set at the bottom of the PCNFs / ZIF8-SA composite aerogel to carry out solar seawater desalination and collect the salt extracted from the side; battery-grade Li2CO3 powder can be obtained by treating its aqueous solution with carbonate, thereby realizing the collection of lithium ions in seawater.

Citation Information

Patent Citations

  • Oil-water separation type sodium alginate / graphene oxide composite aerogel and preparation method thereof

    CN106853296A

  • A method for preparing a highly stable, biodegradable dual-network oil-water separation membrane

    CN108905296B

  • High flux high efficiency nanofiber membranes and methods of production thereof

    CN102481527A

  • Corn straw oil stain adsorbent for oil field, and preparation method thereof

    CN111330554A

  • Integrated multifunctional solar evaporator and preparation method thereof

    CN117209000A

Cited By

  • Porous floating type evaporator based on dynamic rotary self-cleaning and preparation method and application of porous floating type evaporator

    CN120364784A

  • A porous floating evaporator based on dynamic rotating self-cleaning and a preparation method and application thereof

    CN120364784B

  • Multi-level EC-ZP-coated ESi-P solar evaporator based on bionic double-channel structure and preparation method of multi-level EC-ZP-coated ESi-P solar evaporator

    CN120483315A